Harnessing of Mini Scale Hydropower for Rural Electrification in Nepal - Ghimire, Hari Krishna (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
This paper provides insight on hydropower development in general and mini-scale hydropower in particular, for rural electrification in Nepal. It also analyses the opportunities and challenges in the development of mini-scale hydropower to supply reliable electricity in remote rural areas of the country as an aid to poverty reduction and economic progress. Hydro Nepal: Journal of Water, Energy and Environment Vol. 1, No. 2(2008) pp. 26-28